Prevalencia de moscas paleteras (Haematobia irritans) en bovinos de la parroquia Quiroga, cantón Bolívar - Montoya Yumbo, Orlin Angelo (2025)
The present study aimed to determine the prevalence of the horn fly (Haematobia irritans) in cattle from the Quiroga parish, Bolívar canton. The research was conducted using a quantitative-qualitative approach, non-experimental, cross-sectional, and correlational in design. A sample of 495 cattle across 11 farms was studied during the dry season, applying direct observation, structured surveys, and photographic records. The variables analyzed were prevalence, most affected body regions, and control methods used. An overall prevalence of 86% was found, with a progressive increase in mean values from 36.33% in October to 72% in December. Statistical analysis revealed significant differences between the months evaluated (p < 0.047). The most affected body regions were the withers and scapula (16.67%) and the back (13.59%). Although regional differences were not statistically significant (p > 0.05), key areas for control were identified. Additionally, 100% of farmers reported weekly monitoring of fly presence, and 64% applied insecticides, although 36% questioned their effectiveness. Seventy-three percent reported difficulties in applying treatments, and 27% indicated parasite resistance to products. In conclusion, the high prevalence of H. irritans represents a persistent threat to cattle health and productivity in the region, highlighting the urgency of implementing more effective and sustainable control strategies, accompanied by technical training for producers.